Integrating Eco-ELT in ESP to Foster Green Communication Competence: Evidence from Indonesian Polytechnic - Dian Heriani; Evi Agustina Sari; Trisna Hidayati (Penerbit dan Percetakan CV. Picmotiv, 2026)
Vocational higher education is increasingly expected to prepare graduates who possess not only profession-oriented English proficiency but also the ability to communicate responsibly about sustainability issues. Despite growing interest in Ecological English Language Teaching (Eco-ELT), its integration into English for Specific Purposes (ESP) within polytechnic education remains underexplored. This study investigates how Eco-ELT can be integrated into ESP to foster Green Communication Competence, drawing evidence from polytechnic institutions in Indonesia and China. Employing a mixed-methods design, data were collected through questionnaires and semi-structured interviews involving ESP lecturers from both institutions. Quantitative data were analyzed descriptively, while qualitative data were examined using thematic analysis to identify pedagogical practices, institutional support, implementation challenges, and strategies for integrating sustainability into ESP instruction. The findings reveal that lecturers across both institutions demonstrate positive attitudes toward embedding sustainability into ESP learning. However, successful implementation depends on teacher readiness, institutional commitment, curriculum support, the availability of sustainability-oriented teaching materials, and collaboration with industry partners. Evidence from the two polytechnic contexts suggests that Eco-ELT strengthens Green Communication Competence by connecting language learning with authentic environmental and professional communication tasks. The study concludes that Eco-ELT provides a practical pedagogical framework for transforming ESP instruction in vocational higher education and contributes to preparing environmentally responsible graduates capable of participating in sustainable professional practices.